Komunikasi Lingkungan dalam Kinerja Berkelanjutan UKM di Indonesia (StudiKasus terhadap UKM Tulip Craft dan Kopi Salarea) - Ismaeni, Fahrul (UI Scholars Hub, 2022)
This study aims to formulate an environmental communication strategy for the sustainable performance of SMEs in Indonesia. Taking the case of Tulip Craft and Salarea Coffee, this is qualitative research with a case study approach. After conducting observations, interviews with informants with purposive sample criteria and literature studies regarding the concept of sustainable performance and environmental communication, the results of this study indicate that Tulip Craft and Salarea Coffee SMEs implement sustainable performance in their business because they consider aspects of business profits (profit), social empowerment (people) and the impact of the natural environment (planet). Tulip Craft puts it into practice through environmentally friendly products whose production often involves residents as a form of social empowerment. Meanwhile, Salarea Coffee does not specifically sell environmentally friendly products. Their profits are channelled to the Salarea Foundation to carry out environmentally friendly activism such as the construction of the Salarea Garbage House and barista training for Special Educational Needs students in Garut. In conclusion, SMEs can implement sustainable performance with environmental communication strategies that run pragmatic and constitutive elements through two lines: environmentally friendly and “non-environmentally friendly” products. Either way, it must lead to profit as a prerequisite for social empowerment and environmentally friendly products/activities.